Integrated Database Development Food and Nutrition Training Program on SEAMEO RECFON - Dodi Suswandi; Ivan Hanafi; Muhammad Yusro (Indonesian Journal of Multidisciplinary Science, 2022)
The Southeast Asian Ministers of Education Organization Regional Center for Food and Nutrition (SEAMEO RECFON), already has a pretty good system, but there are some problems and the need for up-to-date information on food and nutrition topics and service facilities that support all activities. To support the process of monitoring and evaluating program achievement targets. SEAMEO RECFON requires a database system not only for operations but also for monitoring and evaluation needs. The system must be able to store and manage data on the results of achievements from program activities, document the results of analysis and other information. In this study, an Integrated Database System has been designed and implemented to achieve the achievement of training programs in the field of food and nutrition, using the System Development Life Cycles (SDLC) method with a prototyping development model that helps in system development. This system can store and collect various types of achievements along with related information such as student data, teacher data, school data, types of training, research programs, and other detailed information that supports the research process. The system also provides a feature for users to be able to report and submit data on participants and guidance schools and new colleagues. The system is implemented in prototype form and tested against functionality, performance, and security. The results expected by the Integrated Database system can help the operations of the Organizational Staff both for operations and an integrated data collection process and facilitate the process of monitoring and evaluating program achievement targets.